2017
DOI: 10.1002/alr.22052
|View full text |Cite|
|
Sign up to set email alerts
|

Air pollutants may be environmental risk factors in chronic rhinosinusitis disease progression

Abstract: Air pollutants correlate with CRS symptom severity that may be influenced by exposure levels, with a more pronounced impact on CRSsNP patients. This study is the first to demonstrate the possible role of inhalant pollutants in CRS phenotypes, addressing a critical knowledge gap in environmental risk factors for disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
74
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 48 publications
2
74
3
Order By: Relevance
“…Mady et al showed that PM 2.5 was significantly associated with incidence of FESS with a 1.89‐fold increased risk in need for FESS in the CRSsNP population with each unit increase in PM 2.5 ( p = 0.015). Furthermore, worse symptom levels were seen with increasing exposure to BC in patients with CRSsNP, with SNOT‐22 scores increasing by 7.97 points with each 0.1‐unit increase in BC ( p = 0.0008) …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Mady et al showed that PM 2.5 was significantly associated with incidence of FESS with a 1.89‐fold increased risk in need for FESS in the CRSsNP population with each unit increase in PM 2.5 ( p = 0.015). Furthermore, worse symptom levels were seen with increasing exposure to BC in patients with CRSsNP, with SNOT‐22 scores increasing by 7.97 points with each 0.1‐unit increase in BC ( p = 0.0008) …”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, worse symptom levels were seen with increasing exposure to BC in patients with CRSsNP, with SNOT-22 scores increasing by 7.97 points with each 0.1-unit increase in BC (p = 0.0008). 4 The comparative analysis of distribution of air pollutants based on residence demonstrated that overall PM 2.5 concentrations were significantly higher in Pittsburgh compared with other locations in Allegheny County. In our study, the subgroup analysis between the studied groups (AERD, CRSwNP, and CRSsNP) showed that mean PM 2.5 and BC were not significantly different between the study groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRS is a multifactorial disease that is characterized by significant goblet hyperplasia, mucus hypersecretion, mucociliary dysfunction, and persistent sinonasal inflammation. The etiology of CRS is not well known, but air pollution, particularly fine particulate matter (particulate matter ≤2.5 μm, PM2.5), a major air pollutant, is a principal environmental risk factor for CRS, as evidenced by population studies . Compared with coarse particles, PM2.5 is considered to be more harmful to the human respiratory system due to its smaller diameters and larger surface area to absorb various toxic substances.…”
mentioning
confidence: 99%